Impact of Building Information Modelling in achieving Sustainable Efficiency - Kavanancheeri, Linsy (Journal of Accounting, Business and Management (JABM), 2024)
This review paper explores into the impact of Building Information Modelling (BIM) implementation on sustainable efficiency within construction projects. It systematically examines BIM’s influence on sustainable project performance, its utilization in construction organizations, and the identification of barriers and enablers affecting the integration of sustainable practices through BIM, with recommendations to overcome these barriers. Methodologically, the review synthesizes extensive literature on BIM in construction field is conducted through systematic searches across databases like Scopus and Google Scholar from 2006 to 2024. The findings reveal BIM’s transformative role in the construction industry’s digital evolution, enhancing collaboration, design clash detection, cost estimation, and scheduling, with promising potential for environmentally conscious design through its integration with sustainable practices. Nonetheless, challenges such as high adoption costs, expertise limitations, and software compatibility hinder widespread BIM implementation, particularly in sustainability-focused projects. The study underscores the immense potential of BIM in supporting sustainability within construction, emphasizing the necessity for guidance, training, modified business models, and collaborative efforts to unlock its full potential. This review bridges the gap between BIM’s potential and practical implementation, providing insights into leveraging BIM for sustainable construction practices, thereby promising a more environmentally conscious future for the construction industry.